Use of thromboelastometry in assessing bleeding or thrombotic risks in a patient with congenital dysfibrinogenaemia. Issue 2 (25th September 2013) - Ang, King‐Sin; Morrison, Gary
Summary: A 74‐yr old woman with congenital dysfibrinogenaemia presented with an ischaemic foot requiring a below knee amputation. She had recently undergone popliteal artery angioplasty and was transfused fibrinogen concentrate prior to the procedure. She had no known bleeding or thrombotic episodes in the past, and had not undergone genetic profiling to determine potential phenotypic presentations. On this admission, thromboelastometry was used which demonstrated a prothrombotic trace. A decision was made to withhold transfusion and surgery proceeded uneventfully. We recommend thromboelastometry as a point‐of‐care tool that could be used to provide quick information in aiding perioperative coagulation management of patients with inherited bleeding disorders.